2017
DOI: 10.1063/1.4996629
|View full text |Cite
|
Sign up to set email alerts
|

Determination of LEDs degradation with entropy generation rate

Abstract: We propose a method to assess the degradation and aging of light emitting diodes (LEDs) based on irreversible entropy generation rate. We degraded several LEDs and monitored their entropy generation rate (Ṡ) in accelerated tests. We compared the thermoelectrical results with the optical light emission evolution during degradation. We find a good relationship between aging and Ṡ (t), because Ṡ is both related to device parameters and optical performance. We propose a threshold of Ṡ (t) as a reliable damage … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 31 publications
0
12
0
Order By: Relevance
“…The entropy generation rate can be described as the input power (P) at a certain temperature (T). Normally, the internal heat generated during the operation of electronic devices, such as resistors [11], capacitors [12], LEDs [13], is conducted into the external environment. The entropy generation of a resistor is introduced as a typical example below.…”
Section: Entropy Methodologies For Electronic Devicesmentioning
confidence: 99%
See 4 more Smart Citations
“…The entropy generation rate can be described as the input power (P) at a certain temperature (T). Normally, the internal heat generated during the operation of electronic devices, such as resistors [11], capacitors [12], LEDs [13], is conducted into the external environment. The entropy generation of a resistor is introduced as a typical example below.…”
Section: Entropy Methodologies For Electronic Devicesmentioning
confidence: 99%
“…Following a similar idea to that for resistors, Cuadras et al [12] investigated the entropy characterization of overstressed capacitors for lifetime prediction and found that entropy generation was related to capacitor parameters, including capacitance, structural size, and operating voltage. Subsequently, Cuadras et al [13] carried out a similar investigation into LED lights and determined the entropy generation rate with LED degradation. A thermodynamic damage parameter S(t) was proposed to project an LED lifetime.…”
Section: Entropy Methodologies For Electronic Devicesmentioning
confidence: 99%
See 3 more Smart Citations